Effects of principles of corporate governance on management of early childhood education in Bahati Division Nakuru County - Kithuku, Roselyne M. (My University, 2014)
This study sought to examine the effects of principles of corporate governance on management of early childhood education (ECE) in Bahati Division Nakuru County, Kenya. These were necessitated by the desire to establish whether schools are applying principles of corporate governance in managing school affairs. Proper application of corporate principals enables achievement of stated goals in management of ECE. The study draws a correlation between adoption of principals of corporate governance and performance of the ECE sector. Thus the study seeks to determine the effects of principles of corporate governance on management of ECE in Bahati Division, Nakuru County, Kenya. These were guided by the following objectives; To examine a basis for an effective corporate governance in ECE management in Bahati Division, Nakuru North Sub-County; To establish rights and equitable treatment of shareholders in ECE management in Bahati Division, Nakuru North Sub-County; To analyze the role of stakeholders in ECE management in Bahati Division, Nakuru North Sub-County ; To determine adherence to the principle of full disclosure and Transparency in ECE management in Bahati Division, Nakuru North Sub-County. The research adopted a descriptive survey design. This was suitable in this study as it helped the researcher establish the existing levels of compliance with principals of corporate governance at the ECE schools and their influence on performance. It further allowed identification of standards and norms with which to compare the stakeholder’s involvement in proper management of ECE in the Division. This eventually impacts curriculum implementation. The target population was 41 ECE centers in Bahati Sub-County and 123 teachers in the same area. A sample of 11 pre-school teachers, 10 pre-school head teachers and 10 preschool committee members was taken for the study. A pilot study was carried out on a different set of respondents to better plan for the research. The test-retest procedure was used for testing reliability and it yielded favorable results to warrant reliance on the data collected and its findings. Qualitative and quantitative data was obtained through questionnaires. This was further analyzed and presented through narratives, tables and graphs. The study revealed that there are clear guidelines in observing principals of corporate governance. These include division of labor, especially among supervisory employees and especially the board of management. The school board should make known the legal and regulatory requirements to key personnel in the schools under study in order to ensure they appreciate and adhere to principals of corporate governance. In agreement with Crawford (2007), the management ought to be able to fulfill its duties and responsibilities irrespective of those who do not act in accordance to stated guidelines. The study recommends the Involvement of all stakeholders in all aspects of the management of ECE as a way of observing adherence to principals of corporate governance.